The Relationship between Knowledge and Behavior of Local Communities in Maintaining Environmental Conservation: Literature Review - Suhendrinal Suhendrinal; Abdul Razak; Nurhasan Syah; Skunda Diliarosta (Postgraduate School, Universitas Negeri Padang, 2023)
This study aims to determine the relationship between knowledge and behavior of local communities in preserving the environment. This type of research is research that uses the literature review method. Literature review research is a method in research to identify, evaluate, and interpret research results that are relevant to a particular research topic, or phenomena that are the focus of research conducted by reviewing scientific articles in a structured and planned manner. In this study, it is known that knowledge has a relationship with people's behavior in maintaining, managing, and utilizing the environment properly without damaging the environment. This is based on the knowledge gained that makes people aware of the importance of protecting the environment so that it can be used by the next generation.